2007
DOI: 10.1039/b612142j
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional chelators for copper radiopharmaceuticals: the synthesis of [Cu(ATSM)–amino acid] and [Cu(ATSM)–octreotide] conjugates

Abstract: Two new bifunctional chelators that are derivatives of the bis(thiosemicarbazone) ATSMH(2) proligand have been prepared, one with two phenyl carboxylate substituents on the exocyclic nitrogens (L(1)H(2)) and one with a single phenyl carboxylate (L(2)H(2)). The new ligands have been characterised by NMR spectroscopy, mass spectrometry and in the case of L(1)H(2) by X-ray crystallography. The copper, nickel and zinc complexes of the new ligands have been synthesised and characterised. Electrochemical measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 25 publications
0
45
0
Order By: Relevance
“…[22][23][24] It has been suggested that complexes that retain the dimethylated backbone are less susceptible to reduction and, thus, more practical for use in delineating hypoxia. 18 To this end, bis(thiosemicarbazones) containing carboxylate 25 and hydrazine groups 26 at the N-terminus have been recently synthesized and conjugated to octreotide and glucose, respectively, though little biological and radiochemical data has been published on these complexes, so it is unknown how these modifications affect their hypoxic selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] It has been suggested that complexes that retain the dimethylated backbone are less susceptible to reduction and, thus, more practical for use in delineating hypoxia. 18 To this end, bis(thiosemicarbazones) containing carboxylate 25 and hydrazine groups 26 at the N-terminus have been recently synthesized and conjugated to octreotide and glucose, respectively, though little biological and radiochemical data has been published on these complexes, so it is unknown how these modifications affect their hypoxic selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…The carboxylic acid functionality was used to attach different peptides, including octreotide, a somatostatin analog with improved pharmacological properties ( Figure 3). [50,51] However, the first in vitro and in vivo study of a functionalized bis(thiosemicarbazone) involved the functionalization of a thiosemicarbazide with an aromatic group bearing different functionalities, such as a hydroxyl, a nitro, or even a nitroimidazol moiety. Some of the examples proved to be hypoxia selective in vitro and in vivo, although with a high liver uptake, pointing to the necessity of opening new directions into the field of functionalization of these compounds, so as to bypass limitations in liver biodistribution.…”
Section: Multimodal Imagingmentioning
confidence: 99%
“…71 4.1 Syntheses 4.1.1 Compound 5. It was prepared as described by Cowley et al 43 Thiosemicarbazide 3 (1.00 g, 9.51 mmol) was dissolved in water (17 ml) and treated with 5.5 ml conc. HCl at 10°C in a 100 ml round-bottom flask.…”
Section: Methodsmentioning
confidence: 99%
“…A typical synthesis protocol consists of two steps: preparation of the ( pro)ligand by condensation of a dicarbonyl compound with two thiosemicarbazide molecules, followed by metallation with an appropriate metal salt. 43,44 Condensation of two different thiosemicarbazides to a dicarbonyl (leading eventually, to dissymmetric M(btsc) complexes), can also be performed, but a good control of reaction conditions during synthesis, is required to avoid formation of unwanted side products. 45 For our syntheses we used a slightly modified synthetic procedure as we did not isolate any of the intermediates.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation